2019
DOI: 10.4314/ijbcs.v13i3.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of <i>Plasmodium falciparum</i> malaria infection on serum cortisol, adrenocorticotropic hormone, pregnancy associated plasma protein-A and alpha-fetoprotein in pregnant women at Nnewi

Abstract: The present study assessed the maternal cortisol, Adrenocorticotropic hormone (ACTH), Pregnancy associated plasma protein-A (PAPP-A) and alpha-fetoprotein (AFP) concentrations in malaria infected pregnant women. A total of 76 (40 apparently healthy pregnant and 36 malaria-infected pregnant) women aged 18-40 years were prospectively recruited. Early morning blood samples (5 ml) were collected from each subject at 1 st and 2 nd trimesters. 1 ml of whole blood was used for the diagnosis of P. falciparum malaria u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(26 reference statements)
0
1
0
1
Order By: Relevance
“…Infection with the human immunodeficiency virus type 1 in pregnant women represents an independent risk factor for maternal mortality and adverse pregnancy outcome [28]. Previous report has shown that immune hyperactivity to paternal antigens has been hypothesized to play a role in the development of hypertension in pregnancy, and the immunosuppression caused by HIV could temper the immune response at the placental site and reduce placental vasoconstriction [29]. This potential protection may be a function of the intensity of immunosuppression and may depend on the severity of HIV disease and the use of antiretroviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with the human immunodeficiency virus type 1 in pregnant women represents an independent risk factor for maternal mortality and adverse pregnancy outcome [28]. Previous report has shown that immune hyperactivity to paternal antigens has been hypothesized to play a role in the development of hypertension in pregnancy, and the immunosuppression caused by HIV could temper the immune response at the placental site and reduce placental vasoconstriction [29]. This potential protection may be a function of the intensity of immunosuppression and may depend on the severity of HIV disease and the use of antiretroviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Il s'agit d'une pathologie causée par cinq agents pathogènes (Doutoum et al, 2019) dont le Plasmodium falciparum qui est le plus responsable des cas graves de paludisme et le plus fréquemment rencontré en Afrique de l'Ouest (Bekono et al, 2020). Certains groupes de population sont plus à risque de paludisme et sont plus exposés à ses conséquences parmi lesquels on cite les enfants de moins de 5 ans, les gestantes, les personnes vivant avec le VIH, les sujets en visite dans les pays endémiques (Ukibé et al, 2019;Abossie et al, 2020). La fréquence, la sévérité et l'issue du paludisme sont influencées par les facteurs sociodémographique, environnemental, économique, culturel et comportemental (Hasyim et al, 2019).…”
Section: Introductionunclassified